(untitled) (مجلة إحالات, 2025)
لم يكن الأدب بمعزل عن التأثر بالثورة التي يسجلها التاريخ اليوم لصالح التكنولوجيا بزعامة الحاسوب وشبكة الانترنت ، بل اقتحمت عليه رقته وغازلته فاستدرجته أو تكاد ، ليظهر ذلك في حلة جديدة تتلاءم مع متغيرات العصر التي لم تكن متاحة قبل أن تعرف التكنولوجيا طريقها إلى الحياة ، وتؤثر فيها بما في ذلك الإبداع الأدبي . فالمتلقي قد يجد في طبيعة الأدب التفاعلي أنه يتماس مع العديد من النظريات النقدية الحديثة التي طال الكلام عليها في فترات زمانية مختلفة ، ولعل أكثر النظريات اتساقا مع الأدب التفاعلي نظرية التلقي ونقد استجابة القارئ ، لذلك نسعى من خلال هذه المداخلة إلى التوقف عند كل من الأدب الرقمي وجدلية الإنتاج والتلقي ، في سعي لفهم أثر التغير الذي طرأ على العملية الإبداعية ( الرقمية ) وعناصرها من خلال نموذج التلقي . ّّّّوملا كان هكذا جاءت هذه الدراسة لتحاور النص الرقمي موضحة جمالية التفاعل الحاصل بين املبدع واملتلقي ، ومؤكدة في الوقت نفسه أنه ما يحمله من جماليات ال يمكن للنص الورقي أن يستوعبها ، كما حاولنا من خالل هذه الدراسة أن بنين الفارق ألاساس ي بين مبدع رقمي يمتلك وعيا وثقافة ،وآخر ال يهتم إال بالقشور واملحاكاة الخارجية للعصر ، رغبة في تمكين نفسه من تلك الصبغة الحداثية ، فيأتي إبداعه خال من الجماليات معبرا عن ذهنية خاوية وفقيرة فنيا وأيديولوجيا Abstract : Literature was not isolated from being influenced by the revolution recorded by history today in favor of technology led by the computer and the Internet, but stormed it paper and flirting Aststdrjh or almost, to show this in a new situation adapted to the variables of the era that were not available before the technology knew its way to life, and affect it Including literary creativity. The recipient may find in the nature of interactive literature that it is in contact with many modern critical theories long talked about in different time periods, and perhaps the most consistent theory with interactive literature the theory of receipt and criticism of the response of the reader, so we seek through this intervention to stop at each of digital literature The dialectic of production and reception, in an effort to understand the impact of the change in the creative process (digital) and its elements through the model of receipt. Whereas this study came to dialogue with the digital text, explaining the aesthetic interaction between the creator and the recipient, and at the same time asserted that it carries aesthetics that the paper text can not absorb, as we tried through this study that Benin the fundamental difference between a digital creator possesses awareness and culture, Another is concerned only with the crusts and external simulation of the era, a desire to enable himself of that modernist character, comes his creativity free of aesthetics expressing empty mentality and poor technically and ideologically.